Impact of bronchiolitis guidelines publication on primary care prescriptions in the Italian pediatric population - Elisa Barbieri (npj Primary Care Respiratory Medicine, 2021)
Abstract In Italy, two clinical practice guidelines for the diagnosis and treatment of bronchiolitis were published in October 2014 and December 2015. We evaluated prescriptions for bronchiolitis in children aged 0–24 months before (December 2012–December 2014), in between (December 2014–December 2015) and after (December 2015–December 2018) the guidelines publications. Data were retrieved from the Pedianet database; the measured outcomes were prescriptions rates of antibiotics, corticosteroids, β2-agonists, and other respiratory drugs. In 1011 out of 1581 episodes, patients received at least one treatment, with a total of 2003 prescriptions. The rate of treated bronchiolitis decreased from 66% to 57% (p < 0.001) after the publication of the second guideline; the highest reduction was in younger patients (from 57% to 44%, p = 0.013). Overall antibiotic prescriptions rate did not change, with 31.6% of the patients still receiving them. Our results confirm unnecessary non-evidence-based treatments in the primary care setting, with few changes after the guidelines publications.